A NEEDS ANALYSIS QUESTIONNAIRE FOR THE L2 CLASSROOM: INSIGHTS FROM A BRAZILIAN STUDY ON TASKS AND TECHNOLOGY - Trevisol, Juliane Regina (Revista X, 2020)
Having in mind the importance of pilot studies for empirical investigations in applied linguistics, this article aims to describe a needs analysis instrument which was used as part of a study combining tasks & technology (ELLIS, 2003; GONZÁLEZ-LLORET, 2016) for second/foreign language teaching in Brazil. In addition, the goal is to assist other practitioners who want to design classroom activities integrating digital technology into their practice. For that, the design and implementation of the needs analysis questionnaire is explained and data from seven learners of English as a foreign language (EFL) are analyzed. Overall, results suggest some relevant insights gained from such a proposal, regarding for instance the consideration of learners’ linguistic and digital abilities, which may inform teachers when planning tasks for their language classes. Furthermore, for researchers, this movement reinforces the essentiality of conducting pilot studies as a way to reflect upon instruments, participants and specific contexts, therefore informing better routes for both research and pedagogical practices in different language learning and teaching environments.